Knickpoint evolution in a supraglacial stream. Issue 2 (3rd April 2019) - Kamintzis, J. E.; Irvine-Fynn, T. D. L.; Holt, T. O.; Jones, J. P. P.; Tooth, S.; Griffiths, H.M.; Hubbard, B.
ABSTRACT: Despite numerous studies of knickpoints in bedrock and alluvial channels, no detailed description of knickpoint change on ice has been reported to date. This paper presents the first investigation of knickpoint evolution within a supraglacial stream. Repeat longitudinal profile surveys of a knickpoint on Vadrec del Forno, Switzerland reveal a step height increase of 115 mm and upstream migration of 0.26 m over three days during the 2017 ablation season. Rates and magnitudes of erosion vary spatially across the knickpoint in relation to differing discharge regimes. At high discharges (∼0.013 m 3  s −1 ), erosion is focused at the step base; at low discharges (∼0.003 m 3  s −1 ), erosion is focused on the reach upstream of the knickpoint, at the step lip and the step-riser face. This results in replacement of knickpoint morphology, driven by frictional thermal erosion and hydraulic action. Pool formation further influences step morphology, inducing secondary circulation and increased melt at the base of the step-riser, causing steepening. Results highlight the complexities of water flow over knickpoints, demonstrating that the stream power law does not accurately characterise changing knickpoint morphology or predict retreat rates. Although morphological similarities have been reported between supraglacial and bedrock/alluvial channels, knickpoints in non-ice-walled channels will not necessarily respond to discharge similarly to those on ice due to the different erosional processes involved.